Some intertidal and shallow water polychaetes of the Caribbean coast of Costa Rica - Dean, Harlan K (Universidad de Costa Rica, 2017)
The polychaete fauna of the Caribbean coast of Costa Rica has been inadequately characterized with only nine species previously reported. Collections of polychaetes from intertidal coralline rocks and several shallow sub-tidal sites on the Caribbean coast of Costa Rica have been examined and 68 species were identified. Of these, 66 are new records for Costa Rica.